1996
DOI: 10.1002/ibd.3780020105
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease mucosal biopsies have specialized lymphokine mRNA profiles

Abstract: : Crohn's disease (CD) and ulcerative colitis (UC) are idiopathic inflammatory bowel diseases (IBD) that are characterized by chronic intestinal inflammation and are associated with abnormalities of peripheral and mucosal immune function. The aim of our study was to determine whether CD or UC is characterized by discrete profiles of intestinal lymphokine production. Total cellular RNA was isolated from biopsies of healthy controls and from patients with IBD. Messenger RNA transcript levels in biopsies were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Some IBD patients have a decreased mucosal IL-4 production [26] and in some experimental colitis models, such as in IL-2 knockout mice [27], IL-4 production is down-regulated. In contrast to CD, UC has no such typical Th1 cytokine pattern [23,28]. In DSS-induced colitis, a UC-like model, IL-4 secretion is up-regulated during its chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Some IBD patients have a decreased mucosal IL-4 production [26] and in some experimental colitis models, such as in IL-2 knockout mice [27], IL-4 production is down-regulated. In contrast to CD, UC has no such typical Th1 cytokine pattern [23,28]. In DSS-induced colitis, a UC-like model, IL-4 secretion is up-regulated during its chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in previous studies conducted by ourselves and others, it has been shown that human UC is associated with elevated IL-5 secretion and normal IFN-␥ secretion; nevertheless, it cannot as yet be called a Th2 inflammation because it is not associated with elevated IL-4 secretion, the usual driving force of Th2 responses. On the other hand, established Crohn's disease is quite definitely a Th1 inflamma-tion since IL-12 and IFN-␥ secretion is elevated and there is no increase in either IL-4 or IL-5 secretion (2)(3)(4)(5)31). On this basis, it seems reasonable to suggest that oxazolone colitis is a murine model related to but not identical to UC, whereas TNBS colitis is a model related to Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with experimental models of colitis, very few data have been published concerning the mucosal IL-10 levels in patients with Crohn's disease or UC (30)(31)(32). Recently, Autschbach et al have found a relative elevated expression of IL-10 by inflammatory mononuclear cells in IBD that may be not sufficient to control the production of proinflammatory cytokines such as IL-1 (33).…”
Section: Il-8 and Il-i0 In Pouchitismentioning
confidence: 99%